Experimental study of the effect of oxygen in argon as a shielding gas on corrosion behaviour of dissimilar weld joints of austenitic and ferritic stainless steels. Issue 1 (1st July 2022) - Bakhla, Markush; Yadav, Ajaykumar Udayraj; Kumar, Binod
Abstract: In this study, Austenitic AISI 304L stainless steel was welded with Ferritic AISI430 stainless steel by MIG–welding using welding electrode ER347 and pure Ar and Ar+2%O2 as the shielding gases. The welded samples were polished and dipped into different concentration of HCL solutions of 0.1M, 0.2M, 0.3M and 0.5M concentrations. Weight change of the samples per week in different concentration of HCL solution was noted for 4 weeks and with the help of weight loss, corrosion rate was calculated. The percentage weight loss was observed to be more when welding was done using pure-Ar as a shielding gas compared to Ar+2%O2 . Welded samples were also characterized by means of microscopic and electrochemical investigation.